The changing gender distribution of paid and unpaid work in New Zealand - Paul Callister (New Zealand Government, The Treasury, 2005)
This paper explores five main questions regarding the gender distribution of work, primarily in the context of couples with young children. These are: how much total paid and unpaid work is carried out in New Zealand?; how is this work shared between women and men?; how does this compare with other countries?; how might the mix of unpaid and paid work change in New Zealand in the future?; and should gender equity in paid and unpaid work be a key part of the discussion about labour market participation rates? Overall, the data on paid and unpaid work show a pattern that is universal in industrialised countries. New Zealand men undertake more paid work, while women undertake more unpaid work. But there are differences between countries in the amount of paid and unpaid work undertaken by women and men. In particular, New Zealand stands out in terms of both the long hours worked by a group of men and, despite strong growth in maternal employment in recent decades, the low employment rates of a group of women with young children. Recent attention has focused on social policies which may potentially increase maternal participation rates or their hours of work. However, less attention has been given to how this might change the distribution of paid and unpaid work both within households, and the total amount of work undertaken by individuals and households. This paper considers such issues, and also canvasses some of the reasons why as a society we might want to increase women's participation or hours of paid work. It suggests that such discussions need to be carried out within the context of debates around a wider range of issues including the impact of "overwork" on a group of individuals, families and wider society; how to support replacement fertility levels; and how to increase business productivity. The paper argues that choices made by individuals, households, employers and the government will all play a part in determining the amount of paid and unpaid work undertaken in New Zealand; how such work is distributed between women and men; and the levels of income, parental care of children and leisure that individuals and households are able to achieve.
Keywords: J10; J21; J22; 330; employment; labour supply; gender equity; time use; New Zealand